DIGITALISASI PRODUK UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT EKONOMI SYARIAH - Ririn Anjelina (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
The digital transformation in the era of the Fourth Industrial Revolution has significantly influenced the development of the Islamic economy in Indonesia. This study aims to analyze the role of product digitalization in improving community welfare, particularly through the empowerment of sharia-based micro, small, and medium enterprises (MSMEs). A descriptive qualitative approach with field research was employed, involving in-depth interviews, observations, and document studies with MSME actors, sharia fintech providers, and Islamic economic experts. The findings indicate that digitalization, through sharia-compliant e-commerce and fintech platforms, enhances market accessibility, improves the efficiency of halal product distribution, and strengthens financial inclusion. However, major challenges remain, including low digital and financial literacy, limited technological infrastructure in remote areas, and regulations that do not fully support the application of sharia principles in emerging technologies. To address these challenges, collaborative policy strategies among the government, private sector, and society are essential to build an inclusive, secure, and sustainable digital ecosystem. Digitalization has the potential to serve as a catalyst for achieving maqashid sharia, fostering equitable, transparent, and sustainable welfare for all segments of society.